Perforation of esophagus and subsequent mediastinitis following mussel shell ingestion - Park, Il Hwan; Lim, Hyun Kyo; Song, Seung Woo; Lee, Kwang Ho (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Esophageal perforation is a very rare occurrence because accidental swallowing of foreign bodies is uncommon in adults. Thus, perforation due to swallowing of a foreign body and subsequent development of mediastinitis is rarely encountered by physicians. We experienced such a case and described an adult male patient who had perforated esophagus after accidentally swallowing a mussel shell. The patient visited our emergency department complaining of painful dysphagia for 4 days. A review of history revealed that he consumed a spicy seafood noodle soup containing mussel shells 4 days ago. Computed tomography (CT) of the chest showed the foreign body in the esophagus and pneumomediastinum was identified. We removed the mussel shell fragment using rigid esophagoscopy; explo-thoracotomy, debridement of mediastinal abscess and irrigation were performed.